2010
DOI: 10.2478/s11756-010-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis in mature zygotic embryos of Picea likiangensis

Abstract: Somatic embryogenesis (SE) was successfully induced from mature zygotic embryos of seven families of Picea likiangensis (Franch.) Pritz after 20 weeks culture on initiation medium. Three basal media (one-half strength LM medium, one-half strength LP medium and improved LP medium) with different concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D) and 6-benzyladenine (6-BA) were tested but only one-half strength LM medium supplemented with 2,4-D and 6-BA was successful for the embryogenic cultures (EC) init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…We found that the best response time for EC induction was from late July to early August, about 9–10 weeks after fertilization. Moreover, the later embryogeny ranging from pre-cotyledon to early cotyledon embryo stage were the most responsive to induction of the ECs for initiation of SEMs, which is similar to the reports that pre-cotyledon embryos in later embryogeny were benefit for SE, while cotyledonary stage embryos were less successful in pine species 14 , 37 , 38 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found that the best response time for EC induction was from late July to early August, about 9–10 weeks after fertilization. Moreover, the later embryogeny ranging from pre-cotyledon to early cotyledon embryo stage were the most responsive to induction of the ECs for initiation of SEMs, which is similar to the reports that pre-cotyledon embryos in later embryogeny were benefit for SE, while cotyledonary stage embryos were less successful in pine species 14 , 37 , 38 .…”
Section: Discussionsupporting
confidence: 86%
“…In 1985, SEMs was produced for the first time in a coniferous species, Picea abies 11 . In subsequent years, SE technology has been successfully applied in many coniferous species 12 – 14 . Numerous studies have successfully regenerated SEMs by selecting the appropriate explant type 15 , species/genotype 16 and plant growth regulator (PGR) in coniferous plants SE studies 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Although many conifers (e.g. Abies, Larix, Pinus, Picea, and Pseudotsuga) exhibit SE (Chen et al, 2010) there are still problems associated with the induction of SE and the production of somatic seedlings. For example, it is still very difficult to produce embryogenic tissue (ET) from vegetative tissues of mature conifers, thus the process can be very time consuming, costly, and inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…PEG is a non-permeating osmoticum that increases desiccation tolerance and induces the deposition of storage proteins in cells (Attree et al, 1991;Misra et al, 1993;Heringer et al, 2013). The positive effect of PEG on embryo maturation has been reported for many coniferous species, including Picea abies (Hudec et al, 2016), P. likiangensis (Chen et al, 2010), P. glauca (Stasolla et al, 2002;Stasolla & Yeung, 2003), and Cryptomeria japonica (Maruyama et al, 2007). Hosoi and Maruyama (2012) reported a 25-fold increase in the number of mature embryos produced in Pinus luchuensis, relative to the number of mature embryos produced in PEG-free medium when embryogenic tissue was incubated on a medium containing 15% PEG.…”
Section: Introductionmentioning
confidence: 99%
“…Much more data on the successful initiation of somatic embryogenesis in mature embryos have been obtained to date for representatives of other taxonomic groups of conifers. Thus, embryogenic cultures were derived from mature zygotic embryos of Pinus geradiana, P. kesya, P. koraiensis, Abies alba, A. nordman nia na, A. balsamea, A. fraseri, Picea abies, P. glauca, P. mor risonicola, P. likiangensis, P. omorika, and others (Yeung, Thorpe, 2005;Vooková, Kormuťák, 2007;Chen et al, 2010;Shuklina, Tret'yakova, 2019). A significant disadvantage of using juvenile material (zygotic embryos) as explants for clonal propagation, including using somatic embryogenesis, is the impossibility of using the material from plants whose genetic potential has already appeared phenotypically (adult trees with strictly defined characteristics) (Bonga, 2017).…”
mentioning
confidence: 99%